PENGUATAN KARAKTER KEBANGSAAN PADA SEKOLAH BERBASIS KEAGAMAAN DI KECAMATAN BAKI, KABUPATEN SUKOHARJO (STUDI KASUS DI SMA ISLAM AL-AZHAR 7 SUKOHARJO) - Widiatmaka, Pipit; Muchtarom, Moh (PKn Progresif, 2015)
The result of research showed that the implementation of nationality character reinforcement in SMA Islam (Islamic Senior High School) Al-Azhar 7 Sukoharjo included: 1) Civic education, Al-Qur?an Education, Sociology and History subjects addressing the nationality character, 2) the presence of Javanese language subject, the part of language variety in Indonesia, 3) boy scout activities, 4) OSIS (Internal School Student Organization) activities, 5) flag ceremony, and 6) celebration of RI?s independence day. The constraints the educator faced in building the nationality character reinforcement included: 1) the educator always play game online leading to laziness in learning, 2) SMA Islam Al-Azhar 7 Sukoharjo should attend two curriculums: one from Al-Azhar foundation and one from Sukoharjo Regency?s Education and Culture Service; thus educator found difficulty in integrating both curriculums, 3) However the nasionalism character is the part of the religion nasionalism, sometime the student didn?t care about the character it self. The nationalism attitude demonstrated by the educators of SMA Islam Al-Azhar 7 Sukoharjo, included: 1) participating actively in flag ceremony implementation, 2) participating actively in boy scout activities, 3) speaking good and correct Indonesian, 4) expressing opinion when Indonesia is in conflict with other states, 5) participating in heroic and independence days celebration, 6) being proud of diversity existing in Indonesia, 7) loving nationality and heroic songs, 8) being care of fellow human beings, and 9) being care of environment.